The rise of actualistic taphonomy in South America - de Francesco, Claudio German (2025)
Over the past four decades, global actualistic taphonomy studies have grown significantly, driven by increased interest in present day patterns and processes of fossilization. South America has mirrored this trend, though the exact growth level is unclear. This study compiles actualistic taphonomy research in South America based on internationally accessible journal articles and book chapters using databases such as Web of Science, ResearchGate, Google Scholar, and Academia. Results revealed a steady rise in studies from 1985, with Argentina leading, followed by Brazil, Uruguay, and a few other countries with lesser representation. Terrestrial environments have seen the most extensive research, largely due to archaeologists and vertebrate paleontologists, with marine environments (mainly mollusk-based studies) following. Freshwater actualistic taphonomy began in 2006 and was the next most commonly represented, while estuarine and lagoonal environments were the least studied. Most research has been naturalistic: examining taphonomic patterns, taphofacies, live-dead fidelity, and time-averaging. However, experimental studies increased markedly after 2009. Synthesis papers appeared from 2007, reflecting the growing body of literature. Archaeological studies have been the most prolific, with vertebrate studies dominating the region’s actualistic taphonomy literature, followed by research on mollusks and lithics. Brachiopods, foraminifera, diatom, pollen, and phytoliths have developed less. Several groups, including plants, arthropods, worms, lichens, charcoal, pottery, rock art paintings, and sediments, remained poorly studied, highlighting the need for further research. This review underscores the significant progress made in South American actualistic taphonomy but also points to underrepresented environments and taxonomic groups that should be addressed in future studies.